Factors Affecting Students' Interest In Working As Public Accountants - Ni Made Gayatri Wulantari; I Gde Ary Wirajaya (International Journal of Economics, Management and Accounting, 2025)
The interest in choosing a career as a public accountant is driven by an understanding of job opportunities, good income prospects, professional recognition, and the alignment between individual abilities and the demands of the accounting profession. This study aims to analyze the factors of labor market considerations, soft skills, financial rewards, and social values on students' interest in working as public accountants. This research was conducted at five nationally ranked universities in Bali in 2024, based on uniRank, with a sample of 315 respondents determined using purposive sampling. This study proves that the theory of planned behavior can be a consideration in career choice determination and that expectancy theory can explain that students consider the outcomes they will receive in that career. Additionally, this research can positively contribute to universities in Bali by identifying the factors influencing students' interest in work, thereby improving the education system to be more focused on the choices or interests of each accounting student. The analysis results show that labor market considerations, soft skills, financial rewards, and social values have a significant positive impact on students' interest in becoming public accountants.